Ecofeminism and Enviromental Protection: A Legal Perspective - Budi Hermawan Bangun (Faculty of Law, Jambi University, 2020)
Women are very important figures to ensure sustainable development. This paper discusses the role of women in environmental protection from the perspective of eco-feminism and law. This research is a non-doctrinal legal research with a socio-legal approach. The data used are secondary data obtained through literature studies, then the data that has been obtained is analyzed qualitatively. It is learnt from the discussion that eco-feminism as a thought that criticizes the dominance of patriarchy over control of environmental management and has succeeded in encouraging environmental protection movements carried out by women in various countries. Women are key actors in using, managing and protecting natural resources. Environmental preservation is closely related to the role of women. From a legal perspective, eco-feminism is an effort by the people to seek justice as the main goal of law and ensure the principle of equality before the law inmonitoring, protecting and enjoying the benefits of environmental sustainability.